Key Plant, Key Pests: Southern Yew (Podocarpus macrophyllus) - Brandon White; Chris Marble; Caroline R. Warwick; Juanita Popenoe (EDIS)
This publication provides information and general management recommendations for dieback, fusarium wilt, root nodules, root rot, aphids, eriophyid mites, and scale. For a more comprehensive guide of woody ornamental insect management, download "Professional Disease Management Guide for Ornamental Plants" (http://edis.ifas.ufl.edu/pp123) or the "Integrated Pest Management in the Commercial Ornamental Nursery" guide (https://site.caes.uga.edu/sehp/files/2020/03/UF-IPM-in-the-Commercial-Ornamental-Nursery.pdf). Additional information on pest management can be found in the 2017 Southeast Pest Control Guide for Nursery Crops and Landscape Plantings (https://content.ces.ncsu.edu/southeastern-us-pest-control-guide-for-nursery-crops-and-landscape-plantings).